2021
DOI: 10.17219/acem/129573
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the clinical differences between COVID-19, SARS, influenza, and the common cold: A systematic literature review

Abstract: Background. This review focuses on the frequency of symptoms in COVID-19 in comparison to SARS, influenza and common cold.Objectives. To evaluate and compare the knowledge about the clinical features, symptoms and differences between patients with COVID-19, SARS, influenza, and common cold. The research can help ear, nose and throat specialists and other health practitioners manage patients during the COVID-19 pandemic. Material and methods.The biomedical databases used in the study included PubMed and MEDLINE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 25 publications
2
11
0
Order By: Relevance
“…Other symptoms reported in 1-10% of patients included dizziness, nausea, headache, chest pain, arthralgia, diarrhea, sputum production, respiratory distress syndrome, and renal disease. These symptoms were also confirmed by other studies [67][68][69]. Conversely, symptoms such as seizure and conjunctivitis were reported in less than 1% of patients.…”
Section: Resultssupporting
confidence: 86%
“…Other symptoms reported in 1-10% of patients included dizziness, nausea, headache, chest pain, arthralgia, diarrhea, sputum production, respiratory distress syndrome, and renal disease. These symptoms were also confirmed by other studies [67][68][69]. Conversely, symptoms such as seizure and conjunctivitis were reported in less than 1% of patients.…”
Section: Resultssupporting
confidence: 86%
“…However, our results are consistent with other studies [ 28 ] as previously stated and provide original data to be confirmed by prospective cohort studies. Moreover, certain symptoms of AR perceived by patients may have been confused with the one from upper respiratory tract infection although apart from nasal obstruction and rhinorrhea they are different [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another important aspect that needs to be taken into consideration, in the current pandemic context, are the similarities between pulmonary COVID-19 lesions and ILD in the anti-MDA5 DM patients, proper differential diagnosis being mandatory [ 5 , 38 , 39 ].…”
Section: Clinical and Paraclinical Featuresmentioning
confidence: 99%